2019
DOI: 10.1111/1750-3841.14806
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Natural and Artificial Sweeteners Compounds in the Sensory Profile and Preference Drivers Applied to Traditional, Lactose‐Free, and Vegan Frozen Desserts of Chocolate Flavor

Abstract: The study developed traditional and light chocolate‐flavor frozen dessert formulations, aimed at the general public, lactose intolerants, and vegans, and evaluated influences on quantitative sensory profiles and consumer acceptance with the replacement of sucrose by sweeteners in low‐calorie versions. Twelve samples with different matrices were studied, sweetened with sucrose, sucralose, and stevia. The ideal concentration of sucrose (9%: dairy samples and 15%: vegan samples) was determined by the JAR scale. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The sweetening power verified for stevia in this study was 95, close to that found by Medeiros et al. (2019) in traditional chocolate flavored ice cream sweetened with 9% sucrose, and Esmerino et al. (2013) in their study with strawberry flavored petit suisse cheese, where both found a sweetening power of 100 for this sweetener.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The sweetening power verified for stevia in this study was 95, close to that found by Medeiros et al. (2019) in traditional chocolate flavored ice cream sweetened with 9% sucrose, and Esmerino et al. (2013) in their study with strawberry flavored petit suisse cheese, where both found a sweetening power of 100 for this sweetener.…”
Section: Resultssupporting
confidence: 88%
“…Through the regression equation, it was possible to reach the values of 13.6% of mango pulp and 8.8% of sucrose. There are several studies which analyze the ideal sucrose in dairy products (Esmerino et al., 2015; Medeiros et al., 2019; Paixão et al., 2014; Souza et al., 2011), elucidating that this concentration varies according to the matrix and even between types of the same product, such as yogurt.…”
Section: Resultsmentioning
confidence: 99%
“…pared vegan ice creams made with sucrose, sucralose, and stevia. Products made with stevia were associated with increased bitter taste, bitter aftertaste, and sweet aftertaste (de Medeiros et al, 2019). Given that there are more generally recognized as safe (GRAS) notices for stevia products than for monk fruit products (38 vs. 4, respectively), it is likely that consumers are more familiar with products made with stevia and perhaps are habituated to these flavor defects.…”
Section: Discussionmentioning
confidence: 99%
“…Stevioside and rebaudioside (Reb) A are the major sweet compounds among the steviol glycosides [ 6 ] and are the most widely used steviol glycosides on the market according to a Mintel Global New Products Database (GNPD) product search [ 7 ]. However, stevioside and Reb A exhibit bitter and licorice off-taste [ 8 , 9 , 10 , 11 , 12 , 13 ], which pose challenges to product formulation.…”
Section: Introductionmentioning
confidence: 99%